2022
DOI: 10.1038/s41531-022-00302-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported periodontitis and C-reactive protein in Parkinson’s disease: a cross-sectional study of two American cohorts

Abstract: Periodontitis triggers systemic repercussions, such as elevated levels of high-sensitive C-reactive protein (hs-CRP). This has never been studied within Parkinson’s Disease (PD). The aim of this study is to compare hs-CRP levels of self-reported periodontitis cases versus cases without periodontitis in PD patients. Data from the National Health and Nutrition Examination Survey (2015–2016 and 2017–2018 waves) were analyzed. PD cases were identified through medication regimens and periodontitis cases through a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…P-values for the presence of Porphyromonas gingivalis were statistically significant in all PK biospecimens (serum, saliva, and RNA; −0.141, −0.141, and −0.103, respectively). This may indicate a special role for this known keystone pathogen, LPS, and gingipains in amplifying systemic inflammation for PK pathogenesis (Adams et al, 2019;Olsen et al, 2020;Jasemi et al, 2022;Lyra et al, 2022). NHANES data have shown that periodontitis is associated with leukocytosis in PK patients (Botelho et al, 2020) underlining an inflammatory context as a well-accepted part of the pathology (Hirsch et al, 2005;Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…P-values for the presence of Porphyromonas gingivalis were statistically significant in all PK biospecimens (serum, saliva, and RNA; −0.141, −0.141, and −0.103, respectively). This may indicate a special role for this known keystone pathogen, LPS, and gingipains in amplifying systemic inflammation for PK pathogenesis (Adams et al, 2019;Olsen et al, 2020;Jasemi et al, 2022;Lyra et al, 2022). NHANES data have shown that periodontitis is associated with leukocytosis in PK patients (Botelho et al, 2020) underlining an inflammatory context as a well-accepted part of the pathology (Hirsch et al, 2005;Lee et al, 2009).…”
Section: Discussionmentioning
confidence: 98%
“…We have recently demonstrated a higher prevalence of periodontitis in PD patients [ 103 ] and possible systemic repercussions with the elevation of circulating white blood cell counts [ 106 ] and c-reactive protein [ 107 ]. In fact, systemic inflammation caused by periodontitis has been hypothesized to develop chronic neuroinflammation and ultimately interfere with PD pathogenesis [ 104 ].…”
Section: Microbial Dysbiosis and α-Synmentioning
confidence: 99%
“…Systemic inflammatory markers, such as CRP, might have a role in early detection of inflammatory oral conditions in PD, together with other systemic inflammatory markers, e.g., WBC, IL-1alpha, IL-1beta, IL-17A and TNF-alpha ( 118–120 ).…”
Section: Dashboard Vital: Nonmotormentioning
confidence: 99%